If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3v + 8)(7 + -1v) = 0 Reorder the terms: (8 + 3v)(7 + -1v) = 0 Multiply (8 + 3v) * (7 + -1v) (8(7 + -1v) + 3v * (7 + -1v)) = 0 ((7 * 8 + -1v * 8) + 3v * (7 + -1v)) = 0 ((56 + -8v) + 3v * (7 + -1v)) = 0 (56 + -8v + (7 * 3v + -1v * 3v)) = 0 (56 + -8v + (21v + -3v2)) = 0 Combine like terms: -8v + 21v = 13v (56 + 13v + -3v2) = 0 Solving 56 + 13v + -3v2 = 0 Solving for variable 'v'. Factor a trinomial. (7 + -1v)(8 + 3v) = 0Subproblem 1
Set the factor '(7 + -1v)' equal to zero and attempt to solve: Simplifying 7 + -1v = 0 Solving 7 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1v = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1v = 0 + -7 -1v = 0 + -7 Combine like terms: 0 + -7 = -7 -1v = -7 Divide each side by '-1'. v = 7 Simplifying v = 7Subproblem 2
Set the factor '(8 + 3v)' equal to zero and attempt to solve: Simplifying 8 + 3v = 0 Solving 8 + 3v = 0 Move all terms containing v to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3v = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 3v = 0 + -8 3v = 0 + -8 Combine like terms: 0 + -8 = -8 3v = -8 Divide each side by '3'. v = -2.666666667 Simplifying v = -2.666666667Solution
v = {7, -2.666666667}
| (x/2)+(x/3)=9/2 | | -x+5=2x+8-4x | | 3x-14=6x+16 | | x+9x-6x-4x=20 | | 25w^2*9= | | 28.3+0.43= | | 5(n-3)-3(2n+1)=19 | | 6x+3=(x+2) | | 7w-15=5(w+1) | | -5(x+2)-3=36+2x | | 2+n=2+8 | | -4x-7/3=29/3 | | 9x+32=3x+86 | | -2x-3(4-2x)=2(x-3)+3 | | 4x-3-x=-15+x | | 2x-3(x+4)=2(x-5) | | 180-x=x+120 | | (m^2-7m-11)by(m-8)= | | 15k-12=10 | | ?4= | | (6)(8)(w)=208 | | 2n=2+8 | | 4(2x-5)=4 | | 4?= | | 12+2(x-9)=3(x-2) | | 2?= | | 3(2x+7)=-20+11 | | -4(-7+8x)=188 | | (4)(8)(w)=208 | | ?2= | | n+(n+1)=206 | | 7y-4+7y=12 |